Alcohol-initiated dediazoniation of aryldiazonium ions to aryl radicals: a simple and efficient route to arylboronates. (1st September 2018) - Zhang, Xiulian; Zhang, Zhicheng; Xie, Yongbin; Jiang, Yujie; Xu, Ruibo; Luo, Yuhui; Tao, Chuanzhou
A simple and efficient access to arylboronates was achieved with methanol-initiated borylation of aryldiazonium salts. Reduction of aryldiazonium ions by single electron transfer from methanol affords aryl radical species, which undergo a subsequent C-B bond formation with bis(pinacolato)diboron. This highly practical borylation process, which can be carried out on the gram-scale, enjoys operational simplicity as well as mild and catalyst-free conditions.